Role of the C Terminus of FtsK in Escherichia coli Chromosome Segregation - Yu, Xuan-Chuan (American Society for Microbiology, 1998)
FtsK is essential for Escherichia coli cell division. We report that cells lacking the C terminus of FtsK are defective in chromosome segregation as well as septation, often exhibiting asymmetrically positioned nucleoids and large anucleate regions. Combining the corresponding truncated ftsK gene with a mukB null mutation resulted in a synthetic lethal phenotype. When the truncated ftsK was combined with a minCDE deletion, chains of minicells were generated, many of which contained DNA. These results suggest that the C terminus of FtsK has an important role in chromosome partitioning.